Teenage girl posing on a playground - Unknown:::Creator::::::::::::
Negative shows a teenage girl wearing a dress posing on a playground which may be at Alum Rock Park in San Jose, California. This is possibly a picture of a member of the YWCA's Contenta Hora group. Contenta Hora was a YWCA club for Latinas.